Global healthgrid : e-Science meets biomedical informatics : proceedings of Healthgrid 2008 - Solomonides, Tony (Studies in health technology and informatics, 2008)
Reflects the diversity of mature practice: Advancing Virtual Communities, that offers a glimpse of the kind of communities brought together by means of collaboration grids; Public Health Informatics, that explores the diffusion of grid concepts and technologies in health informatics; and, Translational Bioinformatics.